Angloscene : compromised personhood in Afro-Chinese translations - Ke-Schutte, Jay, 1980- (University of California Press, 2023)
"Angloscene engages Afro-Chinese interactions within Beijing's aspirationally cosmopolitan student class. Jay Ke-Schutte explores the ways in which many contemporary interactions between Chinese and African university studies are mediated through complex intersectional relationships between whiteness, English, and cosmopolitan aspiration. At the heart of these tensions, a question persistently emerges: how does English become more than a language--and whiteness more than a race? Engaging this inquiry, Ke-Schutte explores twenty-first century Afro-Chinese encounters as translational events that diagram the discursive contours of a changing trans-national political order--one that will certainly be shaped by African and Chinese relations"--